AN ANALYSIS OF ERRORS MADE BY THE FIRST YEAR STUDENTS OF SMA NEGERI 8 PEKANBARU IN WRITING RECOUNT TEXT - Pinanti Pangestasha Pristiwa; Fadly Azhar; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The objective of this research is to find out types of errors made by the first year students of SMAN 8 Pekanbaru in writing recount text. This is a descriptive research The participants of this research were 60 students of class X Science 10 and X Social 2 of SMAN 8 Pekanbaru. The students were selected to be the sample using cluster sampling technique. The writer collected the data by using using writing test which the topic given is “Unforgettable Experience”. The result of this research showed that the students committed error into four types: error of omission, error of addition, error of formation, and error of ordering. From the frequency of each error types, error of formation was the error which most frequently produced by the students. It took 71.90% of the total errors. Moreover, 19.53% errors fell into error of omission and 5.10% errors fell into error of ordering; whereas, for error of addition, it only took 3.47%Key Words: Error, Writing, Recount text.